2001
DOI: 10.1097/00005392-200104000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Nephrostomy Versus Ureteral Stents for Diversion of Hydronephrosis Caused by Stones: A Prospective, Randomized Clinical Trial

Abstract: Our results demonstrated that percutaneous nephrostomy is superior to ureteral stents for diversion of hydronephrosis caused by stones, especially in patients with a high temperature, as well as in males and juveniles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 11 publications
5
52
2
2
Order By: Relevance
“…This is similar to the study done by Mokhmalji et al in which the patients who underwent ureteric stenting had a 9:11 male to female ratio and the patients who underwent Percutaneous nephrostomy had a 12:8 male to female ratio. 3 The sex ratio is also similar to the study conducted by Abdul Ghaffar et al which showed a 1.4:1 male to female ratio. 4 The mean age of patients included in Group A (PCN group) in our study was 45.5±15.83 years and in Group B (DJ Stenting Group) was 50.4±14.45 years.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This is similar to the study done by Mokhmalji et al in which the patients who underwent ureteric stenting had a 9:11 male to female ratio and the patients who underwent Percutaneous nephrostomy had a 12:8 male to female ratio. 3 The sex ratio is also similar to the study conducted by Abdul Ghaffar et al which showed a 1.4:1 male to female ratio. 4 The mean age of patients included in Group A (PCN group) in our study was 45.5±15.83 years and in Group B (DJ Stenting Group) was 50.4±14.45 years.…”
Section: Resultssupporting
confidence: 89%
“…Mokhmalji et al showed a success rate of 100% in PCN group but only 80% rate was achieved in the DJS group. 3 Yagci et al also show a 10,11 Total Leukocyte count was normal in 44% of the patients in our study and raised in 56%. Out of these 32% patients underwent percutaneous nephrostomy and 16% underwent ureteric stenting.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The effectiveness of percutaneous nephrostomy should be given preference over ureteral stents in case initial signs of infected hydronephrosis are detected (16).…”
Section: Commentsmentioning
confidence: 99%
“…There has been some concerns that ureteral stent insertion could increase the risk of exacerbating urinary infection by stone manipulation and that it would be less effective for draining urine as compared with a large-caliber PCN tube [19]. However, previous studies have shown that either PCN or a ureteral stent could effectively relieve obstruction and infection associated with urinary stone [20,21]. Recently, Wang et al reported that, as compared with the insertion of a PCN tube, URS together with a course of strong antibiotics could also be an effective and safe management protocol for fighting sepsis associated with obstructing ureteral stone [22].…”
Section: Discussionmentioning
confidence: 99%